Hydrolysis of extracellular adenine nucleotides by human spermatozoa : regulatory role of ectonucleotidases in sperm function - Romac, Pavle (Array, 2008)
Summary: Evidence is presented for the existence of ectonucleotidases on the membrane of intact human spermatozoa. Enzymes hydrolyze extracellular ATP, ADP and AMP and hence could be described as ecto-NTPDase and ecto-5'-nucleotidase. Suramin, Cibacron 3GA and DIDS, well known ecto-NTPDase inhibitors, caused inhibition of the observed enzyme activity. Enzymatic hydrolysis of ATP, ADP and AMP follows simple Michaelis-Menten kinetics with similar enzyme affinity for all three substrates (Km for ATP, ADP and AMP were (0.395 ± 0.027), (0.401 ± 0.031), (0.517 ± 0.038) mmole dm−3, respectively). Influence of extracellular ATP, AMP, adenosine and cAMP on the parameters of sperm velocity and acrosome reaction was also examined. In normozoospermic samples, ATP and cAMP induced an increase in the amplitude of lateral head displacement and number of acrosomally reacted cells, but not in sperm velocity. However, adenosine and AMP enhanced sperm velocity, without influencing the acrosome reaction. These results show that ATP and adenosine regulate sperm motility parameters in different ways